Antara Stigma dan Realitas Sosial: Status Janda Dalam Pandangan Masyarakat Desa - Salsabila, Destya; Budhi, Setia (Huma: Jurnal Sosiologi, 2024)
The negative stigma that circulates makes people still view widow status with a negative view, even the status is sometimes considered a disgrace. This study aims to describe the society's view of women who have widow status. The theory used in this research is labelling theory. The research approach used is descriptive qualitative, with the type of field research. Semi-structured interviews, participant observation, and content analysis were the data collection techniques used. The research was conducted in Jelapat I Village, Tamban sub-district, Barito Kuala Regency. The data analysis technique went through the stages of data reduction, data presentation and conclusion drawing. The results show that the majority of people in Jelapat I Village have a positive view of widows. The stigma and negative labels that are always attached to widows do not make the community necessarily view widows with a negative view. Widows are given the freedom to do anything in their daily lives without feeling alienated. The community agrees that as long as widows do not engage in deviant behaviour and violate established norms, their status in society is the same. Even so, there is still a small part of the community that views widows negatively. These community members still believe that widows are seducers of their husbands. It can be concluded that the majority of people in Desa Jelapat I already have an open mind and do not discriminate against women just because of their status as widows.  It is hoped that communities in other areas that still hold negative stigmas can follow the example of the people of Jelapat I Village who do not necessarily negatively label widows.